Rethinking the dates of the New Testament : the evidence for early composition - Bernier, Jonathan (Grand Rapids, MI. Baker Academic, 2022)
This paradigm-shifting study is the first book-length investigation into the compositional dates of the New Testament to be published in over forty years. It argues that, with the notable exception of the undisputed Pauline Epistles, most New Testament texts were composed twenty to thirty years earlier than is typically supposed by contemporary biblical scholars. What emerges is a revised view of how quickly early Christians produced what became the seminal texts for their new movement.
The synoptic gospels and Acts: Synchronization -- Contextualization and authorial biography -- The Johannine tradition: The gospel of John -- The epistles of John and Revelation -- The Pauline corpus: Critical matters in dating the Pauline corpus -- The compositional dates of the Pauline corpus -- Hebrews and the letters of James, Peter, and Jude: Hebrews and Jude -- 1 and 2 Peter and Jude -- Early extracanonical writings: 1 Clement and the Didache -- The epistle of Barnabas and the Shepherd of Hermas -- Conclusion.
Includes bibliographical references (pages 281-297) and indexes.
Keywords: Bible. -- Authorship -- Date of authorship; Manuscript dating